ANALISIS LAYANAN PERPUSTAKAAN KELILING DALAM MENGEMBANGKAN BUDAYA LITERASI MASYARAKAT KOTA PALEMBANG STUDI PADA DINAS PERPUSTAKAAN PROVINSI SUMATERA SELATAN DAN DINAS KEARSIPAN DAN PERPUSTAKAAN KOTA PALEMBANG - Nirmala Kusumawatie (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2022)
Mobile library is a mobile library by bringing library materials such as books and others to serve the community from one place to another that has not been reached by the library service settled.. The purpose of this study is to determine the mobile library services of the South Sumatra Provincial Library Service and the Palembang City Archives and Library Service and the obstacles faced by the South Sumatra Provincial Library Service and the Palembang City Archives and Library Service in developing the literacy culture of the people of Palembang. This research is a descriptive qualitative research. The results showed that the mobile library services of the South Sumatra Provincial Library Service and the Palembang City Library and Archives Service were accepted and utilized by the people of Palembang. Mobile library services visit predetermined locations directly and the locations that are used as the point of arrival of mobile library services between the Provincial Library Service and the Palembang City Library Service are different, so that there is no overlap in providing reading services which both aim to improve the reading culture of the community Palembang city.There is an obstacle encountered by the Library Office of South Sumatra Province, namely that it does not have a collection that is included in the entertainment category considering that visitors to mobile library services want a collection that is in accordance with the watch and which is currently becoming a trand topic. Meanwhile, the obstacle encountered by the City Archives and Libraries Service is the lack of competent human resources in the field of Library Science, considering that currently the City Archives and Libraries Service only has one librarian.Keywords: Mobile Library Services, Literacy Culture, City Communities Palembang